(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Vanadium, a heavy metal with insulin-mimetic properties and gastro-protective potentials, has been reported to protect the stomach of healthy rats against aggressive agents like acetic acid. In this study, we investigated the gastroprotective effects of low-dose sodium metavanadate (NaVO₃) in experimental diabetic rats. One hundred male Wistar rats (100-130g) were randomized into two experiments (normal and diseased) with 5 major groups (n=10) each. First experiment included normal (control) and non-diabetic groups treated with varying doses (20mg/kg/p.o, 40mg/kg/p.o, 60mg/kg/p.o and 80mg/kg/p.o) of sodium metavanadate (NaVO3) only. The second experiment included diabetes-induced (65mg/kg/i.p Streptozotocin-STZ) and diabetic groups concomitantly treated with the same doses of sodium metavanadate as in the first experiment. Body weight and blood glucose level (BGL) were measured weekly. After 8 weeks of treatment, gastric acid secretion (GAS) was determined by the continuous perfusion method. Gastric tissue malondialdehyde (MDA), reduced glutathione (GSH), sulfhydryl, nitric oxide levels, Na+/K+ and H+-K+-ATPase pump activities were assessed spectrophotometrically. Gastric tissue histological examination and immunohistochemistry expression of gastric MUC5AC were evaluated. Data were analyzed using two-way ANOVA and were significant at p < 0.05. The BGL was significantly decreased in 20 and 40 mg/kg NaVO₃-treated groups in both non-diabetic and diabetic Wistar groups. Basal GAS significantly decreased in NaVO3-treated diabetic groups. Stimulation with acetylcholine significantly decreased GAS in NaVO3-non-diabetic treated groups. Gastric MDA and GSH were significantly reduced in 60 and 80mg/kg-NaVO3 non-diabetic treated groups. Gastric sulfhydryl and nitric oxide levels were significantly reduced in 20 and 40mg/kg-NaVO3 non-diabetic treated groups. Treatment with NaVO₃ in diabetic groups significantly decreased gastric MDA and sulfhydryl but increased GSH and nitric oxide levels. Gastric H+- K+ ATPase and Na+-K+ ATPase pump activities significantly decreased in diabetic groups treated with 20, 40 and 60mg/kg-NaVO3 compared with the untreated diabetes group. Gastric MUC5AC expression in NaVO₃ non-diabetic and NaVO₃-treated diabetic groups significantly increased compared with control and diabetes alone, respectively. Sodium metavanadate treatment dose-dependently reduced blood glucose levels and improved body weight in diabetic rats. It also modulated gastric acid secretion via the suppression of H⁺/K⁺-ATPase and Na⁺/K⁺-ATPase activities, reduced oxidative stress markers, enhanced antioxidant defences, and increased expression of gastric MUC5AC